Design of Bi-planar coil to suppress radial magnetic field in magnetically shielded cylinder for magnetocardiography - Xie, Xiaoxuan; Zhou, Xiangyang; Zhao, Fengwen; Wang, Weiqian; Yin, Chuanming; Sun, Jinji (Physica scripta, 2024)
The high uniformity coils to suppress the static and dynamic magnetic fields along the cardiac magnetic signal are crucial for obtaining high-quality magnetocardiography (MCG) signals. In this paper, the target field method (TFM) combined with the bald eagle search (BES) algorithm is proposed in the design process of the bi-planar coil (BC) to suppress the radial magnetic field (consistent with cardiac magnetic signal) in the magnetically shielded cylinder (MSC). The simulation signifies that the maximum magnetic field deviation of the designed BC is reduced from 2.87% to 0.58% compared with the BC produced by traditional TFM, which illustrates that the proposed method can effectively suppress the radial static magnetic field of the MSC. In addition, automatic field nulling technology was introduced to suppress the dynamic magnetic disturbance. The experiment shows that the maximum magnetic field disturbance was reduced from 5.3 pT to 2.6 pT in the 4 × 4 measurement array. Finally, the cardiac magnetic signal measurement experiment in the MSC proves that the designed BC system is beneficial for high-quality MCG acquisition.